INFORMATION PROCESSING ON CRIMINAL CONVICTIONS OF A PERSON FOR INVESTIGATIVE PURPOSES - Kāršenieks, Jānis (Administrative and Criminal Justice, 2019)
In the paper, the author analyzes the personal data protection problems of the individuals for investigative purposes in the context of operational actions. In order to understand the essence of the problem, the author of the paper, using legislation and judicial practice, analyzes the essence of the personal data (data relating to criminal offenses, criminal convictions) protection rights to of individuals, the procedure for conducting criminal procedure and operational actions and the necessary amount personal data information.The scientific basis of the research is the normative acts regulating both subjects of research, and judicial practice.The paper addresses the issues, which that have not previously been investigated. The research specifies the criteria, rules and principles, which have to be considered and applied in practice when processing information on individuals’ criminal record for investigative purposes in a operational actions’ context.The aim of the paper is to investigate the guidelines for the protection of natural persons in criminal proceedings while processing information on criminal convictions. The tasks of the investigation are as follows: to analyze the prerequisites for the personal data lawfulness’s processing relating to criminal convictions in the framework of criminal proceedings and operational activities; to identify the cases, in which the criminal prosecutors are entitled to obtain information on a person’s criminal record. The following research methods have been used in the paper: analytical, comparative, inductive, deductive and logical methods.